Identification of identical BAP1 mutations in a patient's peritoneal mesothelioma and mucosal melanoma: A precision medicine case study - Paul Zamiara; Ibrahim Elsharawi; Daniel Gaston; Ryan C. DeCoste; Eoghan Malone; Martin J. Bullock; Mathieu C. Castonguay; Michael D. Carter (Elsevier, 2023)
Biomarker testing has increasingly been adopted in oncology for diagnostic, prognostic, and predictive purposes. Several tumor types undergo reflexive biomarker testing, including immunohistochemistry and next generation sequencing (NGS), to screen for hereditary tumor predisposition syndromes and identify optimal treatment regimens. Routine clinical biomarker testing, however, does not identify less common hereditary cancer syndromes, which instead requires comprehensive genomic profiling (CGP). This report describes the case of a patient with occupational exposure to asbestos who developed peritoneal mesothelioma and experienced a dramatic response to platinum-based chemotherapy. Shortly thereafter, he was diagnosed with metastatic sinonasal melanoma. The uncommon co-occurrence of these two primary malignancies prompted analysis of the patient's mesothelioma by CGP, which identified a pathogenic BAP1 splice site mutation (c.438-1G > A, NM_004656.4, 71 % allele frequency). The melanoma was subsequently evaluated using a clinical NGS panel and found to harbor the same mutation (84 % allele frequency), strongly suggesting that the pathogenic variant is present in the patient's germline (diagnostic of BAP1 tumor predisposition syndrome). These results enabled recommendation of germline testing and suggestion of active clinical trials of targeted therapy to the treating physician, highlighting the important role of CGP in the delivery of precision medicine.